Inside Back Cover: Granular hydrogels for 3D bioprinting applications (View 3/2020). Issue 3 (22nd September 2020) - Cheng, Wei; Zhang, Jing; Liu, Ji; Yu, Ziyi
Abstract : In article number 20200060, Ziyi Yu and co‐workers describe how current challenges of the three‐dimensional (3D) bioprinting could be addressed by using granular hydrogels. Granular hydrogels are shear thinning and seal‐healing, enable higher printing performance and the creation of better physiological conditions for hetero‐cellular constructs. Recent advances in the use of jamming transition of granular hydrogels represent a potential paradigm shift in the 3D bioprinting. This cover art shows the use of granular hydrogels for supporting baths and bioinks in the extrusion‐based 3D bioprinting.